SELECTION CRITERIA FOR GYMNASTICS EXERCISES AT THE INITIAL TRAINING STAGE (Bulletin of Innovative Research, 2026)
This article examines the criteria for selecting exercises during the initial training stage for 7–10 year-old gymnasts. The aim of the study is to identify effective exercises that foster the physical and technical development of children in rhythmic gymnastics and to develop methodological recommendations for selecting these exercises. Based on an analysis of scientific-methodical literature and coaching experience, key criteria for exercise selection were defined: exercises should develop the key physical qualities required in gymnastics (flexibility, balance, strength, coordination); be appropriate to the children’s age-specific anatomical and physiological characteristics; help form the basics of movement technique; and be safe to perform. The study identified priority types of exercises for beginner groups (flexibility/stretching exercises, strength and balance development exercises, fundamental acrobatic elements, as well as exercises without apparatus and with apparatus such as hoop and ball). Results: A 6-month training program following the proposed approach led to significant improvements in children’s flexibility and balance, as well as faster mastery of basic gymnastics elements. Conclusion: Adhering to these criteria when selecting exercises at the initial stage of training increases children’s interest in sports, develops their physical qualities comprehensively, and lays a solid foundation for achieving high athletic performance in the future.